Penggunaan Permainan Peran oleh Guru PAUD untuk Meningkatkan Pembelajaran Sosial-Emosional: Sebuah Studi Kualitatif - Ruth Cinthya Suwandi; Stephanie Riady (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
This qualitative study explores early childhood teachers’ lived experiences in intentionally integrating role-play to support Social–Emotional Learning (SEL) among EY1 children aged three to four years at Kindergarten XYZ Jakarta. The study was conducted within a multicultural and Christian-based early childhood setting involving three EY1 teachers, one school psychologist, and one parent participant. Using a descriptive phenomenological approach, data were collected through classroom observations, semi-structured interviews, and documentation review, then analysed using thematic analysis based on Giorgi’s phenomenological framework. The findings reveal that teachers perceived structured role-play as a meaningful pedagogical strategy that supports children’s emotional expression, empathy, communication, cooperation, and self-regulation through intentional scaffolding and contextualised play experiences. The study further highlights the significance of teachers’ pedagogical sensitivity, flexible facilitation roles, and culturally responsive practices in supporting SEL. The novelty of this study lies in its phenomenological exploration of role-play implementation within an Indonesian faith-informed early childhood context, contributing practical and conceptual insights into sustainable and culturally responsive SEL practices.